Evaluation of the ossification process in newly metamorphosed anurans: applicability of the categorization of long bone mineralization - da Cunha Canevari, Gabriel [UNESP]; Franco-Belussi, Lilian [UNESP]; de Lacerda Valverde, Bruno Serra; De Oliveira, Classius [UNESP] (Springer Nature, 2025)
Analyzing the degree of mineralization can be an excellent tool for evaluating the effects of stressors. Biomarkers that detect sublethal effects on bone structures are highly applicable. The present study proposes to review the categorization technique and apply it to long bones by using four categories to investigate the mineralization of long bones in recently metamorphosed anurans, demonstrating its applicability and efficiency in ecotoxicological studies. The technique involves double staining of bones to differentiate between mineralized and cartilaginous tissues, followed by observation under a stereomicroscope. We used as an applicability model a study of exposure to the insecticide fipronil in two native species, Leptodactylus fuscus (whistling frog) and Scinax fuscovarius (snouted tree frog). To validate the proposed way of application, we also carried out a more complex quantitative analysis and compared the results. We defined four categories that reflected the ossification process during metamorphosis. When applied in the experimental design, these categories proved highly effective in highlighting the effect of the tested contaminant on mineralization. Comparing the results of the proposed methodology with the quantitative analysis showed that both yielded similar outcomes. Thus, assessing the degree of mineralization through the proposed way of analysis is highly applicable and effective and has great potential for analyzing vertebrates’ long bones.
Keywords: Anurans; Ecotoxicology; Long bones; Mineralization; Ossification